2001
DOI: 10.1093/ndt/16.7.1452
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with increased serum levels of cardiac troponins T and I in chronic haemodialysis patients: Chronic Haemodialysis And New Cardiac Markers Evaluation (CHANCE) study

Abstract: Elevated baseline serum levels of cardiac troponins were associated with cardiovascular risk factors, history of ischaemic heart disease and left ventricular hypertrophy in asymptomatic chronic haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 18 publications
9
84
0
3
Order By: Relevance
“…By contrast, cTnI was only increased (50.6 mg/L) in 0.4% of their patients. Iliou et al 50 observed cTnT concentrations 40.1 mg/L in 19% of 258 haemodialysis patients; only 2% demonstrated elevated concentrations of cTnI. Left ventricular mass was associated with cTnT, but not cTnI, concentration, and it has been suggested 49 that LVH may explain the di¡ering behaviour of these markers in haemodialysis patients, with a di¡erent release pattern of cTnT compared to cTnI.…”
Section: Prevalence and Clinical Correlates Of Raised Serum Troponin mentioning
confidence: 99%
“…By contrast, cTnI was only increased (50.6 mg/L) in 0.4% of their patients. Iliou et al 50 observed cTnT concentrations 40.1 mg/L in 19% of 258 haemodialysis patients; only 2% demonstrated elevated concentrations of cTnI. Left ventricular mass was associated with cTnT, but not cTnI, concentration, and it has been suggested 49 that LVH may explain the di¡ering behaviour of these markers in haemodialysis patients, with a di¡erent release pattern of cTnT compared to cTnI.…”
Section: Prevalence and Clinical Correlates Of Raised Serum Troponin mentioning
confidence: 99%
“…We speculate as to the possible causes for the difference in increases in cTnT compared with cTnI. First, increased cTnT but not cTnI reflects increased left ventricular mass in the ESRD population, 26,27 with a different release pattern of cTnT compared with cTnI. Second, cTnT release from injured myocardium may have a longer circulating half-life compared with cTnI because of advanced glycation end products known to accumulate in diabetic patients with renal disease.…”
Section: Apple Et Al Prognostic Value Of Troponin In Renal Disease 2943mentioning
confidence: 96%
“…Una possibile spiegazione è che possano rappresentare, almeno in parte, un danno miocardico subclinico, una risposta infiammatoria al danno cronico renale o a uno stato cronico di sovraccarico di volume a livello cardiaco 56 . La maggior parte degli studi è focalizzata su pazienti emodializzati, nei quali un aumento della troponina è associato all'età, alla concomitante presenza di fattori di rischio cardiovascolare, a una storia di malattia ischemica cardiaca, a diabete e a ipertensione ventricolare sinistra [57][58][59] . Aumentati livelli di troponina nei pazienti sottoposti a emodialisi da lungo tempo sembrerebbero correlare con la mortalità, non solo di natura cardiaca [59][60][61][62][63][64][65] .…”
Section: Cause DI Elevazione Delle Troponine Nel Danno Cardiaco Non Iunclassified